Peran Guru Menggunakan Alat Permainan Edukatif dalam Proses Pembelajaran Anak Usia Dini - Wahyu, Wahyu (Indonesian Journal of Islamic Early Childhood Education, 2018)
The teacher is a model for example that can be used as a child for example, so that the teacher has a very important role for the child. Like wise in the learning process teachers can coordinate how the learning process is good and adapted to the stages of child development. The learning process will be interesting if using media and learning resources that are appropriate in accordance with the learning design. One of them is APE which is a game tool specifically designed that contains elements of education so that it can develop the potential that exists within the child. This study aims to determine the learning process using educational game tools in early childhood education in kindergartens. The method used in this study is a qualitative descriptive method, with a focus on research the role of teachers using educational tools in the process of learning early childhood in kindergarten Private Fruits 2017/2018 academic year. Primary data sources in this study are principals and teachers, secondary data sources in the form of books that can be used as references and journals relating to the role of teachers and educational game tools for children. Data collection techniques used are observation, interview and documentation. To check the correctness of data using triangulation. So that the results of the study show that the role of teachers using APE in the learning process in the Private Fruit Kindergarten has been done well starting from planning, implementation and evaluation. With the existence of APE the process of implementing learning can make it more active and creative so that children can develop all the potential within themselves.